Experience Quality, Satisfaction, and Behavioral Intention among the Visitors of Taman Tamadun Islam (TTI), Terengganu - Nor Hidayah Azhar; Nor Asmalina Mohd Anuar (Universitas Syiah Kuala, 2019)
Objective – Islamic Heritage Park is one of the major exertions of tourism development and experiences as a central concept in tourism research. This study investigates the experience quality associated with Taman Tamadun Islam (TTI) in Terengganu, Malaysia which offers a combination of tourism activities. The purpose of this paper is to examine the relationship of experience quality, satisfaction, and behavioral intention among the visitors of TTI.Design/methodology – A descriptive research was designed for this study to obtain appropriate data using the quantitative approach towards the visitors of TTI. A total of 368 usable questionnaires were analyzed using SPSS to examine the relationship between the variables.Results – Based on the five dimensions of experience quality (architectural, information and education, facilities, quality of services, and activities), four of them except for the facilities were found to have positive effects on visitor satisfaction and behavioral intention. The results also revealed that satisfaction mediates the relationship between experience quality and behavioral intention in the heritage tourism with P value 0.005.Originality/Value – This study discussed the theoretical and management implications of the findings. The suggested strategies in this study would diversify and boost the Terengganu tourism industry by targeting different groups of tourists. The findings of this study have also provided some practical information on the relationship of these variables and recommendations for the improvement of TTI to meet the needs of their visitors in the future.